Exercise intervention for the management of chemotherapy-induced peripheral neuropathy: a systematic review and network meta-analysis - Nakagawa, Natsuki; Yamamoto, Sena; Hanai, Akiko; Oiwa, Ayano; Arao, Harue (Frontiers in Neurology, 2024)
Purpose: Although exercise is recommended for cancer survivors with chemotherapy-induced peripheral neuropathy (CIPN), the effective types of exercise for preventing and treating CIPN remain unclear. This systematic review and network meta-analysis (NMA) aimed to evaluate the comparative effects of exercise on CIPN.Methods: We included relevant randomized controlled trials (RCTs) identified in a 2019 systematic review that evaluated the effects of exercise on CIPN and conducted an additional search for RCTs published until 2023. We evaluated the risk of bias for each RCT; the comparative effectiveness of exercise on patient-reported quality of life (QOL) through an NMA; and the effectiveness of exercise on QOL scores, patient-reported CIPN symptoms, and pain through additional meta-analyses.Results: Twelve studies (exercise, n=540; control, n=527) comparing 8 exercise interventions were included in the analysis. All studies were determined to have a high risk of bias. The meta-analyses showed significantly improved QOL (standard mean differences [SMD] 0.45; 95% confidence interval [CI] = 0.12 to 0.78) and CIPN symptoms (SMD 0.46; 95% CI = 0.11 to 0.82). No severe adverse events were reported. Pain tended to improve with exercise (SMD 0.84; 95% CI = -0.11 to 1.80). An NMA suggested that the interventions of a combination of balance and strength training showed a significant improvement in QOL scores compared to the control. Conclusion: Exercise interventions may be beneficial for improving QOL and CIPN symptoms.High-quality large clinical trials and data are needed to conclude that exercise is beneficial and safe.